Exploring the effectiveness of pre-performance routines in elite artistic gymnasts: a mixed method investigation - Clowes, H.; Knowles, Z. (Science of Gymnastics Journal, 2013)
Competitive sport at the highest level demands consistency and precision in the transfer of skill across various environments, on multiple occasions, in order to produce optimal performance (Singer, 2002). Pre-performance routines (PPR) are sequences of motor, emotional, and cognitive behaviours performed immediately in advance of the execution of self-paced tasks (Cohn, 1990). The purpose of this study was to explore both content and variation of pre-performance routines (PPR) between the four apparatus within Women`s Artistic Gymnastics. Participants were purposely selected from former Great Britain international, female elite artistic gymnasts (n=9). This study employed a mixed-method, phased design. All participants completed the Test of Performance Strategies (TOPS; Thomas et al., 1999) in phase one. A purposeful sampling mechanism using descriptive statistics from questionnaire results generated five profiles for further qualitative exploration as to the application and effectiveness of PPR`s via semi structured interviews. Pen-profiling was used to compare and contrast common themes amongst the preparations for the apparatus. Results indicated differences between vault and beam exercise with regard to pre-performance state and preparation strategies linked to arousal/activation control and cognitive rehearsal. Gymnasts reported prior use of individualised and highly refined routines dominated by imagery and arousal/activation control. Specific PPR strategies were reported for each apparatus with some robust, consistent psychological skills training (PST) components within them. The results from this study demonstrate that each apparatus requires unique preparation strategies with regards to the achievement of an optimal psychological state for performance.